Osa‐miR1873 fine‐tunes rice immunity against Magnaporthe oryzae and yield traits. Issue 8 (19th February 2020) - Zhou, Shi‐Xin; Zhu, Yong; Wang, Liang‐Fang; Zheng, Ya‐Ping; Chen, Jin‐Feng; Li, Ting‐Ting; Yang, Xue‐Mei; Wang, He; Li, Xu‐Pu; Ma, Xiao‐Chun; Zhao, Ji‐Qun; Pu, Mei; et al.
Abstract: MicroRNAs (miRNAs) are known to fine‐tune growth, development, and stress‐induced responses. Osa‐miR1873 is a rice‐specific miRNA targeting LOC_Os05g01790 . Here, we show that Osa‐miR1873 fine‐tunes rice immunity against Magnaporthe oryzae and yield traits via LOC_Os05g01790 . Osa‐miR1873 was significantly upregulated in a susceptible accession but downregulated in a resistance accession at 24 h post‐inoculation (hpi) of M. oryzae . Overexpressing Osa‐miR1873 enhanced susceptibility to M . oryzae and compromised induction of defense responses. In contrast, blocking Osa‐miR1873 through target mimicry compromised susceptibility to M . oryzae and enhanced induction of defense responses. Altered expression of Osa‐miR1873 also resulted in some defects in yield traits, including grain numbers and seed setting rate. Moreover, overexpression of the target gene LOC_Os05g01790 increased rice blast disease resistance but severely penalized growth and yield. Taken together, we demonstrate that Osa‐miR1873 fine‐tunes the rice immunity‐growth trade‐off via LOC_Os05g01790, and blocking Osa‐miR1873 could improve blast disease resistance without significant yield penalty. Thus, the Osa‐miR1873‐LOC_Os05g01790 regulatory module is valuable in balancing yield traits and blast resistance. Abstract : MicroRNAs fine‐tune growth, development, and stress‐induced responses. Herein, we demonstrate that the rice‐specific microRNA Osa‐miR1873 negatively regulates rice immunity against Magnaporthe oryzae, and its proper accumulation plays essential roles in the tradeoffs between blast disease resistance and yield traits via fine‐tuning the expression of LOC_Os05g01790 .